Back to school – The teachers’ worries and needs having a childhood cancer patient or survivor in their class - Otth, Maria; Scheinemann, Katrin (Frontiers in Oncology, 2022)
Background A cancer diagnosis during childhood or adolescence causes nursery and school absences to various degrees. Attending school and meeting classmates gives many children and adolescents some normality back. Nevertheless, it can cause fears and concerns among the teachers. We are currently lacking information about the fears and needs of teachers having a child or adolescent diagnosed with cancer or with a cancer history in their classes. With this study, we aim to close this knowledge gap and assess the teachers’ fears, worries and information needs having a child or adolescent diagnosed with cancer in the class to develop a suitable information tool (flyer). Methods We performed an online survey including teachers covering all grades from nursery to vocational school within the catchment area of our hospital. The survey included separate questions for experience with students still receiving active treatment and those in follow-up care. Answer options included tick boxes and open-ended questions, which we grouped thematically. We used descriptive analysis to describe the survey findings, resulting in a newly developed flyer. Results In total 358 teachers participated in the survey, 80% were female, 63% worked in nursery or primary school. One quarter (26%) had experience with a student diagnosed with cancer. Most teachers with (81%) and without (85%) experience reported at least one concern. The top three concerns reported were: (1) how to inform the class, (2) the resilience of the student and (3) how to deal with the student and his or her family. The teachers preferred oral information by physicians or parents and written information equally. Information on resilience, guidelines with an emergency situation, and the need for cancer-specific information were considered important by about 75-94% of the teachers Conclusion Most teachers reported concerns, which we cover in a newly developed information flyer. However, such a flyer cannot replace individual communication between health care professionals and teachers. The identified concerns are likely to be transferable to other school systems and countries.